Effectiveness of rotavirus vaccines against hospitalisations in Japan - Yoshiyuki Fujii (BMC Pediatrics, 2017)
Abstract Background In Japan, rotavirus hospitalisation occurs at a rate from 2.8 to 13.7 per 1000 child-years among children age less than 5 years, and it imposes a substantial burden to the healthcare system in the country. While both monovalent (RV1) and pentavalent (RV5) rotavirus vaccines are licensed in Japan, neither has been incorporated in the national infant immunization programme. In this study, we estimated vaccine effectiveness (VE) in Japan. Methods This study was conducted in Yuri-Kumiai General Hospital located in a city in the north-western part of Japan. Age-eligible children for rotavirus vaccination were enrolled if they were hospitalized for rotavirus gastroenteritis between September 2013 and August 2016. Rotavirus gastroenteritis was defined by the detection of rotavirus antigen by immunochromatography. “Vaccinated” was defined as infant inoculated with at least one dose of either RV1 or RV5. A conditional logistic regression analysis was performed by modelling the year of birth, year of admission, residence of the children and vaccination status, and by matching the age of cases with that of test-negative controls. The adjusted odds ratio of the vaccinated over unvaccinated was then used to calculate VE in the formula of (1 – adjusted odds ratio) × 100. Results Out of the 244 patients enrolled, rotavirus antigen was detected in 55 (22.5%) of whom 10 (18.2%) were vaccinated, whereas 94 (49.7%) of 189 test-negative controls were vaccinated. During the study period, the vaccine uptake rate in the controls increased from 36.2% to 61.8%. On the other hand, the vaccination coverage over the three years was 64.2% in Yuri-Honjo city (three quarters of the catchment), and 91.4% in Nikaho city (one quarter of the catchment). The VE was calculated to be 70.4% (95% confidence interval: 36.0–86.4%, P = 0.002). The point estimate of the VE was lower but its 95% confidence interval overlaps those of the efficacies obtained from clinical trials in Japan. Conclusion The rotavirus vaccine was effective in the real-world setting in Japan as in the clinical trials, and the introduction of rotavirus vaccine in the national infant immunization schedule will substantially reduce the number of rotavirus gastroenteritis hospitalisation in Japan.